Analysis of triadic interaction between parents, their preterm infants, and a sonorous object - Jánez-Álvarez, María; Moreno-Llanos, Iván; Rodríguez-Garrido, Cintia; De León-Barrios, Yinay José; García-Laredo, Eduardo; Del Olmo-Barros, María Jesús; Rodríguez-Garrido, Cintia (Psychology of Music, 2026)
In the period between birth and approximately 9 months, adults introduce infants to triadic (adult– infant–object) communication. The objective of this study is to explore how early triadic interactions arise and develop in moderate–late preterm infants. We observed and analyzed seven preterm infants at 2, 3, and 4 months of age in triadic interactions with a caregiver and a sonorous object. In the first 2 months of the infant’s life, the responsibility for the interaction rests with the adult. As time went by, parents used a wider range of semiotic systems to communicate with the child, about and through the object. The results demonstrated the presence of triadic interactions in a preterm population beginning in the third month of life. Interaction is structured with the object, its sound, rhythm, and pauses. The parents’ use of pauses was adjusted to the child’s availability. These pauses became longer and more communicative over time, which allowed more participation on the part of the infants. Communication is facilitated by the rhythmic components of the triadic interaction (time/pauses/structure of the interaction sequence).
Keywords: preterm infants; early triadic interactions; parent–child communication; rhythm; gestures